Examining Nurses’ Job Stress and Intent to leave - Omar, Khatijah; Ibrahim, Raja Zirwatul Aida Raja; Halim, Muhammad Abi Sofian Abdul; Mohamad, Zaleha; Johar, Siti Sarawati; Din, Badariah (International Journal of Psychosocial Rehabilitation, 2020)
Many researchers have examined the effects of job stress and majority of them agreed that job stress could affect employee wellbeing at the workplace, increase burnouts, increase absenteeism, reduce employee productivity, and could influence employee’s decision to leave their profession or employer. Because of the harmful effects that job stress offer, therefore, this study aimed to investigate the level of job stress among nurses servicing in several selected public hospitals in the East Coast of Peninsular Malaysia. In addition, the relationship between those nurses’ job stress and intention to leave was also investigated. Data was collected using questionnaires distributed to 450 nurses at those selected hospitals in the East Coast of Peninsular Malaysia. The data obtained by this study was analysed using Statistical Package for Social Science (SPSS) to perform descriptive analysis and also inferential analysis. The findings revealed that nurses who participated in this study had experienced job stress, however their job stress level was higher than average. Surprisingly, the findings also disclose that job stress relates to intent to leave the profession and organization but the relationship is not significant. The findings that are provided by this study could benefit employees as well as employers in nursing field to better understand job stress and its effect on employees’ intention to leave so that programs to reduce job stress at the work place can be designed, thus, can also minimize turnover and in the end can improve retention rate.